Investigation of students' motivation to learn science while studying from home during a pandemic - Raiman, Marsianus; Liu, An Nissa Al Mu’min; Wolo, Daniel (Journal of Research in Instructional, 2021)
This study aims to determine the profile of the motivation for learning science while studying at the homes of class VIII students of SMPN SATAP Taga Laga Buru in lesson 2020/2021. This type of research is descriptive research. The population in this research were all students of class VIII SMPN SATAP Taga Laga Buru, amounting to 36 students, and the sample of this study was 36 students who were obtained by saturated sampling technique. Furthermore, the data collection technique used non-test techniques, namely questionnaires. Data analysis was performed using descriptive statistics. The results showed that the development of the science learning motivation profile while studying at home of the VIII grade students of SMPN SATAP Taga Laga Buru experienced highly motivated (44.44%), motivated (47.23%), moderately motivated (8.33%) less motivated and unmotivated development. motivated (0%). This shows that the profile of motivation to learn Science is quite good. medium.